Reproductive decisions : an economic analysis of gelada baboon social strategies - Dunbar, R. I. M. (Robin Ian MacDonald), 1947- (Princeton legacy library., 1984)
Robin Dunbar uses economic models to explore the social behavior of the gelada baboon (Theropithecus gelada), a unique species, whose social system is one of the most complex among the primates. His work illustrates the value of an approach that views social behavior as being ultimately concerned with reproduction and with the maximizing of an individual's contribution to its species' gene pool. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.